Getting schooled: teachers' views on school-based breastfeeding education in Lebanon - Sara Moukarzel; Christoforos Mamas; Antoine Farhat; Alan J. Daly (BMC, 2019)
Abstract Background School-based breastfeeding education (SBBE) may help improve breastfeeding rates in the long term by instilling in young people a base of evidence-informed knowledge, skills, and attitudes that primes them to make informed decisions about infant feeding and to become positive change agents. Breastfeeding rates in Lebanon remain suboptimal, and breastfeeding misconceptions along with social pressures to use infant formula are known contributing barriers. We conducted this study with pre-K-12 teachers to understand the SBBE landscape as well as the supports and constraints for SBBE at two large Lebanese schools. Methods We conducted a survey with 193 teachers during the 2017-2018 academic school year to collect information about demographics, breastfeeding history, breastfeeding teaching practices, attitudes towards SBBE such as attitude towards educating both boys and girls about breastfeeding, and views on potential constraints to successful SBBE implementation. Descriptive statistics and thematic analysis were used. Binary multiple logistic regression was used to ascertain the effects of teacher characteristics on likelihood to support SBBE. Results While limited SBBE is currently taking place with only eight (4%) teachers reporting teaching about breastfeeding, 133 (69%) reported students should learn about breastfeeding in school. A multiple regression model [χ2(4) = 19.71, p = 0.001] showed teachers were more likely to support SBBE if they/their partners had ever breastfed, if they taught biology, or if they believed that schools should educate both boys and girls about breastfeeding in a society where discussing breastfeeding in public is a taboo. One hundred and ten (60%) teachers reported several concerns to SBBE implementation which included limited uptake by students who might not find SBBE valuable to them and resistance from parents due to cultural barriers. In order to effectively expand SBBE in these schools, 71 SBBE supporters (59.2% of respondents; 13 with missing data) suggested supporting local teachers to deliver SBBE, and 48 (40%) suggested mandating SBBE. Conclusions Teachers held generally positive views on SBBE, which provides a fertile ground for growing SBBE in their schools. Future steps need to include engaging parents, students, and school principals to further understand the social constrains to SBBE before program design.